Prevalência da mordida aberta anterior causada por hábitos deletérios de sucção em crianças de cinco anos de idade - Rosseto, Célia Maria Mamoni (2015)
The malocclusions are oral problems, defined as health issues by the World Health Organization. They represent significant variations in growth and morphology of dental arches, compromising functions and aesthetics of the individual. One type of malocclusion is the open bite, characterized by a deficiency in the normal vertical contact between the antagonist teeth, which may manifest itself in a limited area or, more rarely, in the entire dental arch. When the lack of contact between the teeth is located in the region of canines and incisors, with occlusion in centric relation, this case is called anterior open bite (AOB). It is important to consider that the deleterious oral habits can interfere with normal occlusion and are dependent on factors such as frequency, intensity and duration of this habit. There is a possibility to occur a selfcorrection, since the habit is stopped to the age of three to three and a half years, if the child has a favorable growth pattern. Thus, this study aims to evaluate, by examination of dental occlusion, the prevalence of children with five years old enrolled in the Early Childhood Education Public Schools in Bauru, São Paulo, presenting anterior open bite; get information on deleterious sucking habits of children, through a questionnaire distributed to the parent or guardian; assess the presence of anterior open bite and its association with bottle feeding and deleterious habits of thumb sucking and pacifier. There were examined 1063 children of 2608 enrolled in 62 schools, who match all inclusion criteria. The results have show that among children who had AOB, 60.63% were female and 30.37% male. Of these children, 52.49% reported still present the pacifier sucking habit and 85.97% used it at another time. Among the questionnaire information, it can be emphasized that 79.19% of the mothers of these children could not answer until what age the pacifier could be used. Regarding the finger sucking, 9.95% of the infants still had this harmful habit. It may be concluded a prevalence of AOB in 20.79% of cases; it is necessary to implement educative programs for parents/guardians of children about the theme "Non-nutritive deleterious sucking habits"; between the groups of children without AOB and with AOB, it was noticed diferent behaviors about the breastfeeding time, pacifier sucking and bottle-feeding duration, wherein the use of pacifier was more prevalent than thumb sucking.